2010
DOI: 10.1021/ja908611p
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of the Amino Acid Side Chain and Backbone Contributions to Protein Anharmonicity

Abstract: Elastic incoherent neutron scattering has been used to study the temperature dependence of the mean-square displacements of nonexchangeable hydrogen atoms in powders of a series of homomeric polypeptides (polyglycine, polyalanine, polyphenylalanine and polyisoleucine) in comparison with myoglobin at the same hydration level (h = 0.2). The aim of the work was to measure the dynamic behavior of different amino acid residues separately and assess the contribution of each type of side chain to the anharmonic dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
90
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 29 publications
20
90
0
Order By: Relevance
“…For the msd related to the dynamical transition, these contributions amount to about 0.04 Å 2 at room temperature, in good agreement with what is measured for polyglycine. 8 However, it should be considered that differences between the Mb and aa-m samples related to the side-chains environment, the amount of surface covered by water, the extent of polar/apolar interactions, and the presence of "free" carboxylic and amino groups, could also influence the amplitude of fluctuations. In order to further investigate the role of the polypeptide chain on protein dynamics, we performed inelastic incoherent neutron scattering experiments at a time-of-flight spectrometer with a resolution of 70 μeV fwhm.…”
Section: 27mentioning
confidence: 99%
“…For the msd related to the dynamical transition, these contributions amount to about 0.04 Å 2 at room temperature, in good agreement with what is measured for polyglycine. 8 However, it should be considered that differences between the Mb and aa-m samples related to the side-chains environment, the amount of surface covered by water, the extent of polar/apolar interactions, and the presence of "free" carboxylic and amino groups, could also influence the amplitude of fluctuations. In order to further investigate the role of the polypeptide chain on protein dynamics, we performed inelastic incoherent neutron scattering experiments at a time-of-flight spectrometer with a resolution of 70 μeV fwhm.…”
Section: 27mentioning
confidence: 99%
“…We study poly-glycine (poly-G) and poly-alanine (poly-A) in the dry state (where PDT does not occur) and at a hydration level (h ¼ 0:2 g D 2 O=g HP) low enough to get a signal attributable to protein nonexchangeable H atoms with a negligible D 2 O contribution [15], but high enough to allow the PDT. We have recently shown that hydrated poly-G undergoes only the PDT (no CH 3 are present) while dry poly-A shows only the MGA [3,4]: in this way we are able to study the resolution dependence of the two transitions, separately, avoiding their superposition. The MSD temperature dependence of these systems is compared to that of a representative globular protein, bovine serum albumin (BSA).…”
mentioning
confidence: 99%
“…Molecular origin, physical nature and biological relevance of these ''transitions'' are still matter of discussion. The first one is attributed mainly to thermally activated motions of CH 3 methyl groups [1,[3][4][5][6] (for this reason hereon called methyl groups activation, MGA). The second one, called ''protein dynamical transition'' (PDT), has been first interpreted as a glasslike transition [2] directly correlated to the onset of biological activity [7], but this view has been later challenged.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the temperature increases, new contributions to the dynamics can be triggered. Firstly, the activation of methyl group rotations can be observed [15,16], at temperature values varying from~100 to~180 K, depending on the experimental time resolution [7]. Further increasing the temperature, protein molecules start to fluctuate among different conformational substates, and these fluctuations bring about a steep increase in all measured dynamical properties of the system.…”
Section: Introductionmentioning
confidence: 99%